PERKEMBANGAN, EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PATI TAHUN 2009-2012 (Studi Empiris Pada DPPKAD Kabupaten Pati) - Eny Widayani, 10.05.52.0138; Maryono, Maryono (Students Journal of Accounting and Banking, 2014)
The research aims to analyze the development, effectiveness and contribution of the local tax revenue against the original area of Pati in 2009-2012. It is meant to make regional government district starch can set the right policy in a bid to increase revenue and improve regional tax revenue, as well as looking for a proper solution in solving the problem relating to a decrease local tax revenue. In this research using a method of descriptive data secondary done for measuring a phenomenon in research wit the use of indicators the ratio of regional financial. Population in this research were all data on local tax contained in DPPKAD, whie this sampel is local tax data year periode 2009-2012 contained on DPPKAD. The result showed that the development of the PAD has increased, the greatest growth occurred in the year 2010 amounted to 30,18%. However, the growth of tax areas fluctuates with the level of the greatest development in 2011 of 70,94% caused by the expansion of this type of tax areas. The effectiveness of the PAD and tax areas very effectiveness which is above 100%. Local tax contributions against the PAD still belongs to the largest contribution, less going on in 2011 of 22,48% as a result of the expansion of the types of taxes that tax revenue has increased quite a large area, the lowest contribution occurring in 2012. Contributions per types areas against local atx is very less. The greatest contribution given by street lighting with tax an average contribution per year of 78,60%. While the smallest contribution given by pajak sarang burung wallet that only amounted to 0,08% per year.Keywords: PAD, hotel tax, restaurant tax, entertainment tax, billboard tax, street lighting tax, nonmetallic mineral and stone tax, soil water tax, BPHTB, sarang burung wallet tax.Â